REVIEW ARTICLE: THE COMBINATION USING OF ZN, FE AND CU MAY IMPLICATED IN INDUCED ANEMIA IN PREGNANCY - Khalid Hassan Abdalruda; Bahaa Noor Madhloom (Scholar Express Journals, 2022)
Iron (Fe), copper (Cu), and zinc (Zn) are microelements which important for suitable function of human body. These element are necessary for pregnancy and for normal Fetus development. The rate of complications during pregnancy such as anemia, low birth weight and other depend on normal concentration of these elements. This review aims to verify anemia development in pregnant women due to combined supplementation of Fe, Cu, and Zn. Results :The data exhibit at certain combination dose of these element anemia could be development in pregnancy
Keywords: Anemia; Iron; Zinc; Copper